DETECTION OF FRACTURE A CONTOURS ON the image using expandING MASKS - O. G. Shevchuk; V. Yu. Tsviatkou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The method of detection of fracture a contours based on extensible binary masks is proposed. A comparison of the method developed for performance and stability criteria for localizing the breakpoints (corners) in comparison with the method of Harris when changing the brightness, contrast, and image rotation is held. It is shown that the method is superior to the method of Harris on speed and almost equal in quality of image processing.